TINJAUAN TENTANG PENETAPAN HAK ASUH ANAK DI BAWAH UMUR KEPADA AYAH AKIBAT PERCERAIAN DI PENGADILAN AGAMA PEKANBARU - Syaivanti, Sonia Putri; Lestari, Rika; Darnia, Meriza Elpha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Marriages can break up due to death, divorce, and court decisions. The most commoncause of legal problems that should be given an alternative solutions is the breakdown ofmarriage due to divorce. Divorce can cause several legal consequences, one of which is thelegal consequences for children and their care. In the event of divorce, child custody can begiven to the mother if the child is under the age of 18 years. But it can be ruled out, if thefather can prove if the mother is not eligible for child custody. In this case, the author takesthe example of Decision Number 1513/Pdt.G/2022/PA.Pbr, in this judgment the custody ofthe minor falls to the father, where the minor child needs love and attention from a mother.The purpose of this thesis research is to determine the judge's consideration in determiningthe custody of minors to the father due to divorce at the Pekanbaru Religious Court and tofind out the judge's consideration in determining the custody of minors to the father due todivorce based on the perspective of legal expediency theory.This type of research is a type of sociological research conducted at the PekanbaruReligious Court. The population and samples used are the Pekanbaru Religious Court Judgewho tried the case, the father who litigated, and the mother who litigated. The data sourcesused are primary data and secondary data. The data collection techniques used are literaturereview and interviews.The result of this study is that the judge's consideration in determining the custody ofminors to the father due to divorce in the Pekanbaru Religious Court is that the judge arguesthat Article 105 of the Compilation of Islamic Law letter (a) which explains that themaintenance of children who are not yet mumayyiz or not yet 12 (twelve) years old is theright of the mother. But it is not absolute, because the most important thing is the benefit forthe child himself, then the custody of the child is given to the father because the fatherbehaves better than the mother and the judge's consideration in determining the custody ofminors to the father due to divorce based on the perspective of the theory of legal expediencyin terms of the element of legal expediency has been fulfilled because the decision has had animpact and benefit to the parties and children. The author's suggestion is for the Panel ofJudges, in deciding a case in the future to ensure the condition of children in which field ispreferred for the benefit of children being cared for by mothers, fathers, or jointly and forboth parents, must remain fully responsible for their children without being hindered by timeand situation.Keywords: Child Custody - Divorce - Mumayyiz